1990
DOI: 10.1097/00006199-199007000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Maternal Employment Status Following The Premature Birth of an Infant

Abstract: A sample of 110 two-parent families whose preterm infants were less than 37 weeks gestation, appropriate for gestational age, and free of major congenital anomalies were recruited from two level-III intensive care nurseries. At 3 months postpartum, 40 mothers (36.4%) were employed, 15 (13.6%) stated they were on a leave of absence, and the remaining 55 mothers (50%) were not employed. Although not significantly different on demographic or infant morbidity variables, employed mothers were significantly more emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…In a sample of mothers with teenagers, Shapiro and Mott (1994) also found that as maternal education increased, the proportion of time employed since becoming a mother and the number of weeks employed in the preceding year increased. In their sample of two-parent families with 3-month-old preterm infants, however, Youngblut, Loveland-Cherry, and Horan (1990) found no differences between employed and nonemployed mothers on maternal age or education.Race has been found to have little independent effect on employment status (Leibowitz et al, 1992), but it has shown an interaction effect with mothers' age and education, and husbands' employment attitudes. Employed, married, African American mothers were younger than employed, married, White mothers; however, African American mothers were younger at the birth of their first child than White mothers (Avioli, 1985).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In a sample of mothers with teenagers, Shapiro and Mott (1994) also found that as maternal education increased, the proportion of time employed since becoming a mother and the number of weeks employed in the preceding year increased. In their sample of two-parent families with 3-month-old preterm infants, however, Youngblut, Loveland-Cherry, and Horan (1990) found no differences between employed and nonemployed mothers on maternal age or education.Race has been found to have little independent effect on employment status (Leibowitz et al, 1992), but it has shown an interaction effect with mothers' age and education, and husbands' employment attitudes. Employed, married, African American mothers were younger than employed, married, White mothers; however, African American mothers were younger at the birth of their first child than White mothers (Avioli, 1985).…”
mentioning
confidence: 84%
“…Validity of the scale is supported by the finding that employed mothers had higher HEO scores than nonemployed mothers, and the number of hours employed per week was positively correlated with HEO scores (Youngblut et al, 1990). Cronbach's alphas ranged from .80 to .85 in previous studies of families with preterm infants (Youngblut, 1995;Youngblut et al, 1990), and it was .73 in this study.Maternal Employment Attitude-Behavior Consistency-A computed discrepancy score was used to measure consistency. Mothers indicated the number of hours per week they would prefer to work outside the home.…”
mentioning
confidence: 98%
“…and How satisfied are you with your decision?) were used in studying maternal employment issues for mothers with preterm infants (Youngblut, Loveland-Cherry, & Horan, 1990;1993).…”
Section: Psychometric Performance Of Global Single-item Indicatorsmentioning
confidence: 99%
“…and How satisfied are you with your decision?) were used in studying maternal employment issues for mothers with preterm infants (Youngblut, Loveland-Cherry, & Horan, 1990;1993).Single-item measures have been used frequently in large population surveys such as The quality of American life (Campbell, Converse, & Rodgers, 1976), Social indicators of wellbeing: Americans' perceptions of life quality (Andrews & Withey, 1976), and Functional status and well-being of patients with chronic conditions: Results from the medical outcomes study (Stewart et al, 1989). The use of single-item indicators in clinical research is increasing, especially in the measurement of symptom intensity.…”
mentioning
confidence: 99%
“…Although this finding is limited by missing data, 83% of the women who planned to return to work or school did so. In a sample of mothers of 3-month-old preterm infants, Youngblut, Loveland-Cherry, and Horan (1990) found that intent to be employed was strongly related to employment status. Taken together, these findings indicate that factors other than a high-risk pregnancy influence a woman's employment status after birth.…”
Section: Discussionmentioning
confidence: 98%